GENETIC DIVERGENCE ON QUANTITATIVE CHARACTERS OF EXOTIC MAIZE INBREDS (Zea mays L.) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Forty nine CIMMYT, India Maize inbred lines were characterized based on some morphological traits and grain yield. Genetic divergences of inbred lines of maize were estimated using D2 and principal component analysis. The genotypes under study fell into five clusters. The inter cluster distance were higher than intra cluster distance suggesting wider genetic diversity among the genotypes of different groups. The maximum intra cluster value was observed in cluster IV and minimum in cluster V. The inter cluster D2 values revealed that the maximum distance among the cluster. The highest inter cluster distance was observed between cluster II & I and the lowest inter cluster distance was illustrated in cluster III & I. The cluster means were higher for days to 50% tasseling, days to 50% sillking, plant height, ear height, cob length, number of rows per cob, number of grains per row in cluster IV; cob diameter and grain yield per plant was found higher in cluster II. It is expected that crossing of inbred lines belonging high to medium D2 values tend to produce high heterosis for yield.